2016
DOI: 10.3389/fpsyg.2016.01566
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Classical Kinematics, Entropy, and Fractal Properties As Measures of Complexity of the Motor System in Swimming

Abstract: The aim of this study was to compare the non-linear properties of the four competitive swim strokes. Sixty-eight swimmers performed a set of maximal 4 × 25 m using the four competitive swim strokes. The hip's speed-data as a function of time was collected with a speedo-meter. The speed fluctuation (dv), approximate entropy (ApEn) and the fractal dimension by Higuchi's method (D) were computed. Swimming data exhibited non-linear properties that were different among the four strokes (14.048 ≤ dv ≤ 39.722; 0.682 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 42 publications
2
28
1
1
Order By: Relevance
“…The significant main effect of swimming stroke on FD verified in the present study is in accordance with the scarce literature Barbosa, Goh, Morais, Costa, & Pendergast, 2016). Adding on to their findings, in our work, the swim strokes with higher FD in their swimming patterns, and therefore with a more complex behavior, are the same, independently of sex, expertise and swimming condition: breaststroke followed by butterfly, front crawl and backstroke (the exception is the LK condition, having butterfly the highest FD).…”
Section: Sampensupporting
confidence: 92%
See 2 more Smart Citations
“…The significant main effect of swimming stroke on FD verified in the present study is in accordance with the scarce literature Barbosa, Goh, Morais, Costa, & Pendergast, 2016). Adding on to their findings, in our work, the swim strokes with higher FD in their swimming patterns, and therefore with a more complex behavior, are the same, independently of sex, expertise and swimming condition: breaststroke followed by butterfly, front crawl and backstroke (the exception is the LK condition, having butterfly the highest FD).…”
Section: Sampensupporting
confidence: 92%
“…the more complex and irregular the behavior is. The FD varies according to the swim stroke and the level of expertise Barbosa, Goh, Morais, Costa, & Pendergast, 2016). This study is a follow-up providing evidence that the variations in nonlinear parameters are also dependent on the number of limbs in action, which confirmed the tested hypothesis.…”
Section: Sampensupporting
confidence: 77%
See 1 more Smart Citation
“…Recent papers reported that swimming exhibits nonlinear proprieties but its magnitude differs according to the swim stroke performed (14.048 ≤ dv ≤ 39.722; 0.682 ≤ ApEn ≤ 1.025; 1.823 ≤ FD ≤ 1.919) (Barbosa, Goh, Morais, Costa, & Pendergast, 2016). Of the four swim strokes, front-crawl showed the lowest dv, ApEn and FD (Barbosa et al, 2016). The complexity of the swimming technique also varies depending on the level of expertise.…”
Section: Introductionmentioning
confidence: 99%
“…O nado crawl é considerado a modalidade de maior rapidez entre os quatro tipos de nados competitivos e exercita quase todos os grupos musculares do corpo humano (Jakovljevic;McConnell, 2009;Zamparo et al, 2017). Neste esporte, a parte primordial do controle corporal é a respiração que deve ser eficaz, suave e automática e o nadador de elite tem que trabalhar com equilíbrio a respiração nas três fases: apneia, expiração e inspiração (Cardelli et al, 2000;Cardeli, 2003;Barbosa et al, 2016;Woorons et al, 2016).…”
Section: Discussionunclassified